An Assessment of the Pracharath-Bueng Bang Sue Development Project: A Case Study of Bueng Bang Sue Community, Chatuchak District, Bangkok - Suksamran, Watcharapon (Journal of Human and Society, Sisaket Rajabhat University, 2022)
The purposes of this research were to 1) study the collaborative governance 2) analyze the strengths, weaknesses, opportunities, and threats, and 3) examine the overall operation from the collaborative governance in Pracharath-Bueng Bang Sue development project that consists of the context, input, process, and output. The study was the mixed methods research of qualitative and quantitative. The qualitative research was using the in-depth interview with 8 samples drawn from the private sectors, government sectors, and public sectors using the purposive sampling. The quantitative research used the questionnaires which selected 297 locals in Bueng Bang Sue. The statistical methods used in data analysis were means, standard deviation, and correlation analysis. The findings were as follows: 1. The research of the project found that SCG proceeded the commitment by mutual motivation. It had arisen from the facilitative leadership because SCG was the network leader. SCG supported the project implementation resource and gave the chance to the director-general of Chatuchak District Office to co-design the system. In addition, the overall average was at a high level ( =3.91). 2. The SWOT of the collaborative governance found the strength was clear goals. The weakness was complicated communication. The opportunity was appointed working position in every organization. The threat was the administration was inflexible. The mutual motivation showed that the strength was area understanding. The weakness was ambiguous communication. The opportunity was the locals pay attention to the area development, but the threat was some people do not observe the condition. The ability of collaborative suggested that the strength was the expertness of organization. The weakness was everyone must comply the rule. The opportunity was the other sector supported the cause to the convenient administrative. The threat was people concerned about the changes would happen. 3. The collaborative governance showed that the operation of context, input, process, and output was consistent. In addition, the overall average was at a high level ( =3.94).